Chiral and degenerate perfect absorption on exceptional surfaces - S. Soleymani; Q. Zhong; M. Mokim; S. Rotter; R. El-Ganainy; Ş. K. Özdemir (Nature Communications, 2022)
Robust engineering of non-Hermitian light-matter coupling will be crucial for future optical device design. Here the authors present a photonic system that operates on an exceptional surface, demonstrating chiral and degenerate absorption with super-Lorentzian lineshape.